MARKET ORIENTATION, INNOVATION, AND DIGITAL RESPONSIVENESS IN IMPROVING MARKETING PERFORMANCE OF CULINARY MSMES: A STUDY IN KUDUS REGENCY - Arumsari, Nurul Rizka; Marka, Mira Meilia; Juwariyah, Nurul (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study examines how market orientation and innovation contribute to the marketing performance of culinary MSMEs in Kudus Regency, Indonesia, particularly in the context of increasing digital competition. A qualitative descriptive approach was employed. Data were collected through in-depth interviews, observation, and documentation involving 30 culinary MSME owners selected using purposive sampling. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing to identify patterns linking market orientation, innovation practices, and marketing performance outcomes. The findings indicate that innovation in culinary MSMEs is predominantly incremental and customer-driven. Market orientation is implemented informally through relational closeness and digital responsiveness. The synergy between digital-responsive market orientation and micro-adaptive innovation significantly contributes to improved marketing performance, reflected in sales growth, customer retention, and market expansion. MSMEs should institutionalize simple market intelligence systems and enhance digital engagement strategies to strengthen innovation cycles. This study introduces the concept of micro-adaptive innovation triggered by digital-responsive market orientation in resource-constrained MSMEs, extending classical market orientation theory into informal and digitally fragmented markets.